Pemanfaatan Anggur Laut (Caulerpa racemosa) Sebagai Minuman Fungsional Dengan Penambahan Kayu Manis - Sarvika, Devi; Jamaluddin, Jamaluddin; Sukainah, Andi (Jurnal Pendidikan Teknologi Pertanian, 2024)
This study aims to determine whether there is an effect of adding cinnamon powder to the sea grape functional drink produced. The treatment of adding cinnamon powder consisted of 4 levels, namely without adding cinnamon powder (K), adding 1.5g cinnamon powder (A), adding 2g cinnamon powder (B), and adding 2.5g cinnamon powder (C). By repeating 3 times. The observed variables consisted of tests of functional properties (polyphenols and antioxidants) and hedonic quality (color, aroma and taste) of the functional drink produced. It can be concluded that the addition of cinnamon powder concentration affects the functional properties and hedonic quality of the sea grape functional drink produced. The best sea grape functional drink is produced by adding 2.5g cinnamon powder. This concentration has a polyphenol content of 11.36% and an antioxidant content of 31.66%. The resulting sea grape functional drink with the addition of cinnamon also received good acceptance from the panelists.